High-brightness black PC / ABS alloy material and preparation method thereof

CN117126523BActive Publication Date: 2026-10-16SHANGHAI KINGFA SCI & TECH +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311123894.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2026-10-16
Estimated Expiration
2043-09-01

AI Technical Summary

Technical Problem

然而喷涂工艺不仅对环境有污染,同时成本较高,不再适用于现有流行的车灯无底涂直接真空蒸镀的工艺

Benefits of technology

[0035] The high-gloss black PC/ABS alloy material described in this invention has no obvious appearance defects and can be directly applied in a primerless vacuum evaporation process. It also has ideal impact resistance and heat resistance, which perfectly meets the application requirements of automotive lights. In addition, it has a high-gloss black effect and a high sense of fashion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004427518270000061
    Figure BDA0004427518270000061
  • Figure BDA0004427518270000071
    Figure BDA0004427518270000071
  • Figure BDA0004427518270000072
    Figure BDA0004427518270000072
Patent Text Reader

Abstract

The application discloses a high-black-bright PC / ABS alloy material and a preparation method thereof, and belongs to the technical field of high polymer materials. The product contains specific compound toughening agents and molding modifiers as modified components in a PC / ABS resin system, so that the generation of appearance defects is effectively inhibited, obvious pitting or whitening and mildewing and other appearance phenomena do not occur, the heat resistance is good, the heat distortion temperature can reach above 105 DEG C at the highest, the impact resistance is strong, the processing performance is excellent, the high-bright-black color effect is high, and the product is very suitable for application in the preparation of some bottom-coating-free direct vacuum evaporation process obtained environment-friendly automobile lamp parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer alloy materials technology, specifically to a high-gloss black PC / ABS alloy material and its preparation method. Background Technology

[0002] In the automotive industry, the plastic materials used to manufacture automotive lights mainly include polypropylene, ABS, ASA, and PC / ABS alloys. Among them, PC / ABS alloys have excellent impact resistance, heat resistance, low fogging properties, and appearance, meeting the requirements of automotive light materials for assembly, lighting test standards, and no deformation, cracking, or fogging during use.

[0003] Currently, to achieve better appearance and reflective effects, automotive headlights generally undergo spraying and vacuum evaporation treatments. The former primarily aims to conceal surface defects in injection-molded parts, reduce the precipitation of small plastic molecules, and improve the yield of vacuum evaporation. However, spraying is not only environmentally polluting but also costly, making it unsuitable for the currently popular direct vacuum evaporation process for headlights without a primer. Furthermore, existing primerless processes cannot conceal surface defects such as pitting and white haze, further leading to a lower yield of headlights after vacuum evaporation. While some existing processes add modifiers or reduce the amount of color masterbatch to reduce surface defects, this can negatively impact aspects such as heat resistance, impact resistance, and even brightness. Summary of the Invention

[0004] Based on the shortcomings of existing technologies, the purpose of this invention is to provide a high gloss PC / ABS alloy material. This product contains specific compound toughening agents and molding modifiers as modifying components in the PC / ABS resin system, which not only effectively inhibits the formation of appearance defects, but also has good heat resistance, strong impact resistance, and high gloss black effect.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0006] A high-gloss black PC / ABS alloy material, comprising the following components in parts by weight:

[0007] 60-70 parts PC resin, 20-30 parts SAN (acrylonitrile-styrene) resin, 5-15 parts compound toughening agent, 0.5-2 parts molding modifier, 1-3 parts black masterbatch, and 0.4-1.0 parts processing aid;

[0008] The compound toughening agent includes MBS (methyl methacrylate-butadiene-styrene) copolymer 1 with a particle size of 50-100 nm and MBS copolymer 2 with a particle size of 100-200 nm, wherein the mass ratio of MBS copolymer 1 to MBS copolymer 2 is (1-3):1.

[0009] The molding modifier is bisphenol A-bis(diphenyl phosphate).

[0010] In this invention, the product uses two different MBS copolymers of varying particle sizes as a compound toughening agent to replace the maleic anhydride-grafted ABS commonly used in existing processes. This effectively improves the overall heat resistance and processing performance of the product. Furthermore, the smaller particle size MBS copolymer not only imparts a significant high-gloss black effect to the product but also improves appearance defects that occur during injection molding. On the other hand, the introduction of the larger particle size MBS copolymer compensates for the lower toughening degree of the smaller particle size MBS copolymer. With appropriate proportions, this compound toughening agent can achieve the toughening effect of toughening agents used in conventional PC / ABS alloy materials such as maleic anhydride-grafted ABS. If the proportion of any MBS copolymer is too large or too small, the product will fail to achieve a balance between impact resistance, appearance, and high-gloss black effect. Additionally, if the particle size of the compounded MBS copolymer is inappropriate, it will also be difficult to achieve the aforementioned comprehensive performance improvement.

[0011] After introducing MBS copolymers with varying particle sizes and black masterbatch, specific modifiers are needed to improve the molding performance of the product. In the product described in this invention, bisphenol A-bis(diphenyl phosphate) (BDP) is used as the molding modifier. This substance can significantly improve the molding performance of the product. Simultaneously, it can interact with the colorants in the black masterbatch through adsorption, reducing friction between the colorants in the black masterbatch and improving the dispersibility and flowability of the black masterbatch in the PC / ABS resin matrix. This prevents the product from exhibiting appearance defects such as pitting caused by poor particle dispersion. The inventors have verified that other commonly used molding modifiers in existing PC / ABS alloys cannot achieve the same effect. Furthermore, BDP differs from conventional molding modifiers in the product of this invention; it cannot be excessively introduced, otherwise the product's heat resistance will be severely reduced (in general PC / ABS alloy materials, excessive introduction of such small-molecule molding modifiers usually only reduces the product's toughness).

[0012] Preferably, the particle size of the MBS copolymer 1 is any one or a combination of 50 mm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, and 100 nm.

[0013] Preferably, the particle size of the MBS copolymer 2 is any one or a combination of 100nm, 105nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, and 200nm.

[0014] Preferably, the mass ratio of MBS copolymer 1 to MBS copolymer 2 is any one or a range of two of the following: 1:1, 1.5:1, 2:1, 2.5:1, 3:1.

[0015] Preferably, the PC resin has a melt flow rate of 10-22 g / 10 min at 300°C and 1.2 kg, according to ISO 1133-2012.

[0016] More preferably, the PC resin has a melt flow rate of 10 g / 10 min, 12 g / 10 min, 15 g / 10 min, 18 g / 10 min, 20 g / 10 min, or 22 g / 10 min at 300 °C and 1.2 kg, according to ISO 1133-2012.

[0017] PC resin, as the matrix resin with a large proportion in the product of this invention, affects the heat resistance and processing performance of the product due to its flowability. Verification has shown that when the melt flow rate of PC resin in the product is preferably within the above-mentioned range, the product achieves the best heat resistance, impact resistance, and appearance performance. On the other hand, the flowability of PC resin also has a limited impact on the product's blackness. When the flowability of PC resin decreases, the final product's ability to replicate molds during preparation decreases, especially for high-gloss molds, thus resulting in a certain degree of decrease in the product's blackness. Conversely, if the flowability of PC resin increases, the probability of micro-air marks occurring during processing increases, which also leads to a decrease in the product's blackness. Within the above-mentioned preferred range, the product achieves the best blackness effect.

[0018] Preferably, the SAN resin has a melt flow rate of 25-40 g / 10 min at 220°C and 10 kg according to ISO 1133-2012.

[0019] More preferably, the SAN resin, according to ISO 1133-2012, at 220°C and 10 kg, has a melt flow rate of any one or both of the following: 25 g / 10 min, 28 g / 10 min, 30 g / 10 min, 32 g / 10 min, 35 g / 10 min, 38 g / 10 min, and 40 g / 10 min.

[0020] Similar to PC resin, the flowability of SAN resin in a product also affects the product's heat resistance and processing performance. If the flowability of SAN resin decreases, the product's processing performance will decrease, and the appearance performance may decline. Conversely, if the flowability of SAN resin increases, the product's heat resistance will decrease.

[0021] Preferably, the black masterbatch is a carbon black-loaded SAN masterbatch.

[0022] Preferably, in the high-gloss black PC / ABS alloy material, the sum of the mass percentages of PC resin and SAN resin is not less than 50%.

[0023] More preferably, the carbon black loading is 30-40 wt%.

[0024] More preferably, the carbon black loading is any one or a combination of 30wt%, 32wt%, 35wt%, 38wt%, and 40wt%.

[0025] Preferably, the processing aid is at least one of an antioxidant and a lubricant.

[0026] More preferably, the high-gloss black PC / ABS alloy material comprises 0.2 to 0.5 parts of antioxidant and 0.2 to 0.5 parts of lubricant.

[0027] More preferably, the antioxidant is at least one of hindered phenolic antioxidants and phosphite antioxidants.

[0028] More preferably, the antioxidant is a mixture of hindered phenolic antioxidants and phosphite antioxidants.

[0029] More preferably, the lubricant is PETS lubricant.

[0030] Another object of the present invention is to provide a method for preparing the high-gloss black PC / ABS alloy material, comprising the following steps:

[0031] The components are mixed evenly, then placed in a twin-screw extruder for melt extrusion and granulation to obtain the high-gloss black PC / ABS alloy material.

[0032] The preparation method of the product described in this invention has simple operation steps and can achieve industrial-scale production.

[0033] Preferably, during melt extrusion, the feed section temperature of the twin-screw extruder is 180–220°C, the plasticizing section temperature is 230–250°C, the homogenizing section temperature is 250–270°C, and the screw speed is 300–600 rpm.

[0034] Another object of the present invention is to provide the application of the high-gloss black PC / ABS alloy material in the manufacture of automotive lighting components.

[0035] The high-gloss black PC / ABS alloy material described in this invention has no obvious appearance defects and can be directly applied in a primerless vacuum evaporation process. It also has ideal impact resistance and heat resistance, which perfectly meets the application requirements of automotive lights. In addition, it has a high-gloss black effect and a high sense of fashion.

[0036] The beneficial effects of this invention are that it provides a high-gloss PC / ABS alloy material. This product, by containing specific compound toughening agents and molding modifiers as modifying components in the PC / ABS resin system, not only effectively inhibits the formation of appearance defects and prevents obvious pitting, whitening, or mold growth, but also exhibits good heat resistance, with a heat distortion temperature reaching over 107°C, strong impact resistance, excellent processing performance, and a high-gloss black effect. It is very suitable for use in the preparation of environmentally friendly automotive lighting parts obtained through direct vacuum evaporation without a primer. Detailed Implementation

[0037] To better illustrate the purpose, technical solution, and advantages of this invention, the invention will be further described below with reference to specific embodiments and comparative examples. The purpose of this description is to provide a detailed understanding of the invention, not to limit its scope. All other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of this invention. Unless otherwise specified, the experimental reagents and instruments involved in the implementation of this invention are commonly used reagents and instruments.

[0038] Examples 1-17

[0039] Examples of the high-gloss black PC / ABS alloy material and its preparation method described in this invention are shown in Table 1.

[0040] The preparation method of the high-gloss black PC / ABS alloy material includes the following steps:

[0041] After the components are mixed evenly, they are fed into a twin-screw extruder through the main feed port for melt blending extrusion and granulation to obtain the high-gloss black PC / ABS alloy material.

[0042] During the melt blending and extrusion of the components, the twin-screw extruder is set to 180–220°C, the plasticizing section temperature is 230–250°C, the homogenizing section temperature is 250–270°C, and the screw speed is 500 rpm.

[0043] Comparative Examples 1-9

[0044] The only difference between each comparative example and the embodiment is the type and ratio of components, as shown in Table 2.

[0045] In the components described in each embodiment and comparative example,

[0046] The PC resin 1 is PC 1605T-11, manufactured by Luxi Chemical, with a melt flow rate of 5 g / 10 min at 300℃ and a load of 1.2 kg.

[0047] The PC resin 2 is PC S-2000F, Mitsubishi Japan, with a melt flow rate of 10g / 10min at 300℃ and 1.2kg load;

[0048] The PC resin 3 is PC-1150, Lotte from South Korea, with a melt flow rate of 15 g / 10 min at 300°C and a load of 1.2 kg.

[0049] The PC resin 4 is PC H-2000F, Mitsubishi, Japan, with a melt flow rate of 22 g / 10 min at 300°C and 1.2 kg load.

[0050] The PC resin 5 is PC H-3000F, Mitsubishi, Japan, with a melt flow rate of 30 g / 10 min at 300°C and 1.2 kg load.

[0051] The SAN resin 1 is SAN NX3400, manufactured by Ningbo Taihua, with a melt flow rate of 12 g / 10 min at 220°C and a load of 10 kg.

[0052] The SAN resin 2 is SAN 3027, manufactured by Lihua Yiweiyuan Chemical Co., Ltd., with a melt flow rate of 26 g / 10 min at 220°C and a load of 10 kg.

[0053] The SAN resin 3 is SAN NF2200 AK, manufactured by Ningbo Taihua, with a melt flow rate of 32 g / 10 min at 220°C and a load of 10 kg.

[0054] The SAN resin 4 is SAN KFA-130, manufactured by Kingfa Science & Technology, with a melt flow rate of 40 g / 10 min at 220°C and a load of 10 kg.

[0055] The SAN resin 5 is SAN DG-AS103, manufactured in Dagu, Tianjin, with a melt flow rate of 50 g / 10 min at 220°C and 10 kg load.

[0056] The MBS copolymer 1 is M-701, Kanekachi Chemical Co., Ltd. of Japan, with an average particle size of 75 nm.

[0057] The MBS copolymer 2 is M-521, Kanekachi Chemical Co., Ltd. of Japan, with an average particle size of 180 nm.

[0058] The MBS copolymer 3 is MBS-2821, manufactured by Donghai Plastics, with an average particle size of 250 nm.

[0059] The molding modifier 1 is BDP, manufactured by Jiangsu Yake.

[0060] The molding modifier 2 is silicone masterbatch SI-S50, manufactured by Dongguan Jugo Chemical Technology Co., Ltd.

[0061] The black masterbatch is 6399D, manufactured by Shanghai Cabot Chemical Co., Ltd., a carbon black-supported SAN resin masterbatch with a carbon black loading of 30-40 wt%.

[0062] The antioxidant is a compound of commercially available hindered phenolic antioxidant 1010 and commercially available phosphite antioxidant 168 in a mass ratio of 1:2.

[0063] The lubricant is a commercially available PETS lubricant.

[0064] Unless otherwise specified, all components and raw materials used in the embodiments and comparative examples of this invention are commercially available, and the same type of components and raw materials are used in each parallel experiment.

[0065] Table 1

[0066]

[0067]

[0068] Table 2

[0069] PC resin 3 65 65 65 65 65 65 65 65 65 SAN resin 3 25 25 25 25 25 25 25 25 25 MBS copolymer 1 3 8 6 6 6 6 9 MBS copolymer 2 6 1 3 3 3 3 9 MBS copolymer 3 3 6 Molding Modifier 1 1 1 1 1 0.1 2.5 1 1 Molding Modifier 2 1 Black Masterbatch 2 2 2 2 2 2 2 2 2 antioxidants 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 0.3 lubricant 0.4 0.4 0.4 0.4 0.4 0.4 0.4 0.4 0.4

[0070] To verify the performance of the high-gloss black PC / ABS alloy material described in this invention, the products prepared in each embodiment and comparative example were subjected to the following performance tests, with the specific steps as follows:

[0071] (1) Notched impact strength test of simply supported beam: According to ISO 179-2010 standard, each product was injection molded into an impact specimen with a size of 80×10×4mm. The A-type notch was used for testing, and the impact capacity was 4J.

[0072] (2) Heat distortion temperature test: The test was conducted according to ISO-75-2-2013 standard, and the test conditions were 0.45MPa and 120℃ / min.

[0073] (3) Melt flow rate test: The test shall be conducted in accordance with ISO1133-1-2011, and the test conditions shall be 260℃ and 5kg load;

[0074] (4) Appearance (prickles) test: Each product is injection molded into a 150×100×3mm high gloss board at 260℃ on an injection molding machine. The number of prickles is observed in a standard light box. If the number of prickles in the specified 50×50mm area in the middle is not more than 5, it is considered qualified. If the number of prickles is more than 5, it is considered unqualified.

[0075] (5) Appearance (white fog) test: Visually observe each product and observe the white fog phenomenon in the standard light box. If white fog phenomenon exists, judge the degree of white fog phenomenon as "slight" and "severe".

[0076] (6) Blackness test: The blackness L value of the high gloss board obtained in step (4) is directly tested by X-Rite 7000A. The lower the L value, the better the blackness effect.

[0077] The test results are shown in Tables 3 and 4.

[0078] Table 3

[0079]

[0080]

[0081] Table 4

[0082]

[0083] As shown in Tables 3 and 4, the PC / ABS alloy material of the present invention has high impact resistance, reaching 50 KJ / m. 2 The heat distortion temperature can reach over 100℃, while exhibiting good fluidity, fewer surface pits, no obvious white haze, and a blackness not exceeding 28. As seen in Examples 1-5, as the melt flow rate of PC resin in the product gradually increases, the product's fluidity improves, and the number of surface pits decreases. However, relatively speaking, the product's impact strength weakens, the heat distortion temperature decreases, and the blackness initially increases and then gradually decreases, even causing a slight white haze on the product surface. Therefore, the optimal overall performance is achieved within the range of 10-22 g / 10 min. As seen in Examples 3 and 6-9, as the fluidity of SAN resin in the product increases, the changes in other properties are generally the same as those of PC resin, but the impact strength shows a trend of first increasing and then decreasing. Therefore, the optimal effect is achieved when the melt flow rate of SAN resin is 25-40 g / 10 min. As can be seen from the performance of the products in Examples 3, 10-11, and Comparative Examples 1-2, when the blending ratio of MBS copolymer in the products of the present invention is inappropriate, although it does not affect the flowability or heat resistance of the products, it has a significant impact on the impact resistance and appearance. The MBS copolymer blending ratios of Comparative Example 1 and Comparative Example 2 are not within the limits specified in the present invention, while Comparative Examples 8 and 9 used only a single type of MBS copolymer to prepare the products. Comparative Example 1 exhibited severe white haze, while the impact strength of Comparative Example 2 was only 39 KJ / m. 2 The impact of the supply gap on product 8 is even lower, at 36 KJ / m. 2While Comparative Example 9 exhibits high notched impact strength, its heat resistance is low, and its blackness value is high, neither of which meets practical application requirements. Furthermore, not all MBS copolymer blends can achieve ideal overall performance. As shown in Comparative Examples 3 and 4, blending MBS copolymers with excessively large average particle sizes with small-particle-size MBS copolymers fails to achieve the desired complementary effect. Although the impact strength of both products is improved, their appearance performance significantly deteriorates, exhibiting severe white haze, a sharp increase in surface pitting, and a blackness L-value exceeding 28. As can be seen from Examples 3, 16-17, and Comparative Examples 5-6, in addition to the compounded MBS copolymer, the molding modifier in this invention also has a significant impact on the performance of the product. When the amount of molding modifier added is small, the appearance performance of the product is not ideal and it cannot interact with the color masterbatch. The appearance of the product in Comparative Example 5 has 12 pits. As the amount of molding modifier added increases, the flowability and appearance performance of the product improve, but the impact strength and heat resistance of the product decrease relatively. The heat distortion temperature of the product in Comparative Example 6 even drops to 95°C. Therefore, its addition amount should be maintained at 0.5-2 parts. In addition, the type of additive is not arbitrary. If it is not bisphenol A-bis(diphenyl phosphate), but a type with similar function in the prior art is selected, such as the silicone masterbatch described in Comparative Example 7, the appearance performance of the product cannot be significantly improved.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A high-gloss black material, characterized in that, The components include the following parts by weight: 60-70 parts PC resin, 20-30 parts SAN resin, 5-15 parts compound toughening agent, 0.5-2 parts molding modifier, 1-3 parts black masterbatch, and 0.4-1.0 parts processing aid; The PC resin, according to ISO 1133-2012, has a melt flow rate of 10~22 g / 10 min at 300°C and 1.2 kg. The SAN resin, according to ISO 1133-2012, has a melt flow rate of 25~40 g / 10 min at 220°C and 10 kg. The compound toughening agent includes MBS copolymer 1 with a particle size of 50~95nm and MBS copolymer 2 with a particle size of 105~200nm, and the mass ratio of MBS copolymer 1 to MBS copolymer 2 is (1~3):1; The molding modifier is bisphenol A-bis(diphenyl phosphate).

2. The high-gloss black material as described in claim 1, characterized in that, The mass ratio of MBS copolymer 1 to MBS copolymer 2 is (2~3):

1.

3. The high-gloss black material as described in claim 1, characterized in that, The black masterbatch is a carbon black-loaded SAN masterbatch.

4. The high-gloss black material as described in claim 3, characterized in that, The carbon black loading is 30~40wt%.

5. The high-gloss black material as described in claim 1, characterized in that, The processing aid is at least one of antioxidants and lubricants.

6. The high-gloss black material as described in claim 5, characterized in that, The high-gloss black material comprises 0.2 to 0.6 parts of antioxidant and 0.2 to 0.6 parts of lubricant.

7. The high-gloss black material as described in claim 6, characterized in that, The antioxidant is at least one of hindered phenolic antioxidants and phosphite antioxidants; the lubricant is PETS lubricant.

8. A method for preparing the material according to any one of claims 1 to 7, characterized in that, Includes the following steps: The components are mixed evenly, then placed in a twin-screw extruder for melt extrusion and granulation to obtain the high-gloss black material.

9. The method for preparing the high-gloss black material as described in claim 8, characterized in that, During melt extrusion, the feed section temperature of the twin-screw extruder is 180~220℃, the plasticizing section temperature is 230~250℃, the homogenizing section temperature is 250~270℃, and the screw speed is 300~600rpm.

10. The use of the high-gloss black material as described in any one of claims 1 to 7 in the manufacture of automotive lighting components.

Citation Information

Patent Citations

  • Low-odor and low-emission flame-retardant PC / ABS (polycarbonate / acrylonitrile-butadiene-styrene) composite material and preparation method thereof

    CN106751678A

  • Low-density high-heat-resistant PC / ABS alloy material, and preparation method thereof

    CN107353569A

  • High-blackness PC / ABS alloy material for automotive upholstery and preparation method thereof

    CN110982239A

  • Polycarbonate / polypropylene alloy material, and preparation method and application thereof

    CN111040412A

  • PC / ABS alloy material and preparation method and application thereof

    CN111440429A